Tracking of the growth interface during pvt-growth of SiC boules using a X-ray computed tomography setup - Arzig, Matthias; Salamon, Michael; Uhlmann, Norman; Wellmann, Peter (Materials Science Forum, 2019)
A crystal comprising various polytype switches was analyzed in detail. A very flat temperature profile together with an on axis seed are used to increase the probability for the nucleation of foreign polytypes during growth. Formation of foreign polytype occurred from thin lamella propagating from the edge of the main facet to the crystal rim as well as from 2D nucleation. The evolution of the crystal surface during the growth time is visualized using in-situ XRay computed tomography. Two concurrent growth centers are identified in the beginning of the growth process. Nucleation and lateral growth of foreign polytypes in the main facet area can be traced during the growth process.
CRIS-Team Scopus Importer:2019-09-17
Keywords: Computed tomography; In-situ visualization; Physical vapor transport; Polytype switch; Silicon carbide